Morphological and Morphometric Studies on the Lungs of Himalayan Mongoose (Herpestes edwardsii) - Pathak. V,; Rajput. R,; Shukla. P,; Gupta. D, (Indian Journal of Veterinary Anatomy, 2024)
A mongoose is a small terrestrial carnivorous mammal belonging to the family Herpestidae. The Himalayan mongoose is a brown mongoose species native to the Himalayan region of Indian subcontinent. The specimen under study was collected from road side, as it was hit by a moving car in Palampur (Himachal Pradesh). The specimen was collected and preserved. The dissection was done to record the anatomical observations on the lungs. The lungs were present in the elongated thoracic cavity. The right lung was larger than left and had four lobes, whereas left had only three lobes. The lobes were well demarcated with deep fissures. Right apical, left apical, right diaphragmatic and left diaphragmatic lobes measured 3.31, 3.02, 3.62 and 3.74 cm, respectively.